Reil's Hidden Island: insular cortex and its role in emotional responses, addictions and decision-making (Research, Society and Development, 2021)
Introduction: Supported by recent studies of human neuroimaging, the insula is re-emerging as an important area of ​​the brain, not only in the physiological and homeostatic understanding of the body, but also in pathological contexts in clinical research, implicated in distinct cognitive, affective and regulatory functions, including interoceptive awareness, emotional responses, empathetic processes, decision making and even addictive behavior catalyst. Objective: To investigate insular functions related to emotional behaviors, addictions and decision-making, which are supported by the activation of the insular cortex. Methodology: This is a descriptive research of the integrative literature review type, which seeks evidence on the insular functions related to emotional responses, addictions and decision-making. The search was carried out using PubMed, MEDLINE, Scielo, CDSR, Google Scholar, BVS and EBSCO databases, from 2003 to 2021. Results: The study confirms the necessary role of the insular cortex in the emotional and affective response. Furthermore, the insular cortex of drug users exhibits structural changes, and the activity of the insula during decision-making correlates with the propensity to relapse to use drugs. Furthermore, functional imaging studies in humans have revealed activation of the insula after drug use and craving, and one of the most striking findings of patients with insula lesions is that it stops smoking addiction. Conclusion: The insula has a multitude of functions, which may, at first, present a somewhat confusing picture, and further studies are needed to clarify this complex hidden Isle of Reil.